PENGARUH BRAND IMAGE, PERCEIVED VALUE DAN TRUST TERHADAP NIAT BELI ULANG SALDO E-WALLET GOPAY - Sastrawan, I Gede Agus; Sukawati, Tjok Gede Raka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.06.TAHUN.2021DO - 10.24843/EEB.2021.v10.i06.p03, 2021)
Repurchase appear from the intention of repurchase, repurchase intention is an action taken by the consumer after the purchase process. Components that affect repurchase intentions include brand image, perceived value and trust. This research aims to find out how these components affect GoPay e-wallet users in Denpasar. The sample size used in this study amounted to 140 respondents GoPay e-wallet users in Denpasar City using purposive sampling method on the sampling. Google forms are used to help distribute questionnaires to respondents. This study uses multiple linear analysis techniques as data analysis techniques. This study obtained the results that (1) brand image has a positive and significant effect on the repurchase intentions (2) perceived value has a significant positive effect on the repurchase intention (3) trust has a significant positive effect on the repurchase intention. Based on this research, it is concluded that good brand image, perceived value, and trust greatly influence the repurchase intention of balances on GoPay e-wallet users in Denpasar City.